2021
DOI: 10.3390/ijms22105086
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Pancreatic Cancer: The Interplay of Hyperglycemia and Macrophages Promotes the Acquisition of Malignancy-Associated Properties in Pancreatic Ductal Epithelial Cells

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is still one of the most aggressive solid malignancies with a poor prognosis. Obesity and type 2 diabetes mellitus (T2DM) are two major risk factors linked to the development and progression of PDAC, both often characterized by high blood glucose levels. Macrophages represent the main immune cell population in PDAC contributing to PDAC development. It has already been shown that pancreatic ductal epithelial cells (PDEC) undergo epithelial–mesenchymal transition (EMT) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“… Deng et al (2010) found that the abundant expression of tumor necrosis factor α (TNFα) and interleukin-6 (IL-6) by macrophages can create a favorable inflammatory environment for the occurrence of colonic adenocarcinomas. Moreover, macrophages play a considerable role in the acquisition of the epithelial– mesenchymal transition (EMT) hallmarks observed in gastric cancer tissues ( Guan et al, 2021 ), pancreatic duct epithelial cells ( Otto et al, 2021 ), and tracheal epithelial cells ( Li et al, 2021 ), and EMT signatures plays a vital role in tumor metastasis ( Lu and Kang, 2019 ). Macrophages are heterogeneous cell clusters with intricate functions and forms.…”
Section: Introductionmentioning
confidence: 99%
“… Deng et al (2010) found that the abundant expression of tumor necrosis factor α (TNFα) and interleukin-6 (IL-6) by macrophages can create a favorable inflammatory environment for the occurrence of colonic adenocarcinomas. Moreover, macrophages play a considerable role in the acquisition of the epithelial– mesenchymal transition (EMT) hallmarks observed in gastric cancer tissues ( Guan et al, 2021 ), pancreatic duct epithelial cells ( Otto et al, 2021 ), and tracheal epithelial cells ( Li et al, 2021 ), and EMT signatures plays a vital role in tumor metastasis ( Lu and Kang, 2019 ). Macrophages are heterogeneous cell clusters with intricate functions and forms.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, combined with clinical features, we found the blood glucose were comparatively lower in Im-3 (featured with metabolism). Previous studies have indicated that the alteration of blood glucose levels greatly affected tumor microenvironment and patients’ prognosis [ 68 ]. Consistently, our data indicated blood glucose was negatively associated with overall survival (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tocilizumab has been shown to exert anticancer effects in pancreatic cancer in ex vivo experiments. In a mouse transplantation tumor model, tocilizumab blockade of IL-6 significantly abrogated mesenchymal stromal cell-mediated tumor promotion and delayed tumor formation [ 97 ], and inhibition of IL-6 signaling by tocilizumab partially reversed the EMT phenotype of pancreatic ductal epithelial Kras mutant cells [ 98 ]. PSCs and cancer cells in pancreatic cancer TME release ATP, which activates the P2X7 receptor, promoting PSC proliferation, collagen secretion, and IL-6 secretion, and P2X7R-conditioned cultures also stimulate PSCs to activate the JAK/STAT3 signaling pathway in cancer cells, leading to pancreatic cancer cell migration, which is inhibited by tocilizumab [ 99 ].…”
Section: Stat3 Inhibitors and Cancermentioning
confidence: 99%